EFFECT OF ETHANOL CONCENTRATION ON ZnO NANORODS SYNTHESIZED USING THE HYDROTHERMAL METHOD FOR PARAQUAT WASTE DEGRADATION: PENGARUH KONSENTRASI ETANOL TERHADAP ZNO NANOROD YANG DISINTESIS DENGAN METODE HIDROTERMAL UNTUK DEGRADASI LIMBAH PARAQUAT - Bintang Ramadhan; Iwan Sugihartono; Nurfina Yudasari (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Semiconductor photocatalysts such as ZnO nanorods have been extensively studied for the degradation of water pollutant waste due to their simple, inexpensive, and environmentally friendly process. ZnO nanorods were successfully synthesized using the hydrothermal method on zinc foil substrates with ethanol concentration variations of 10%, 30%, and 50%. The hydrothermal process was conducted for 16 hours at a temperature of 95°C. ZnO nanorods were tested as photocatalysts in a paraquat solution with a concentration of 4 ppm under UV A-B tube luminescent (TL) light for 120 minutes. UV-Vis spectroscopy testing was performed every 30 minutes during the photocatalysis process to determine the photocatalytic efficiency of ZnO nanorods in degrading paraquat waste. The UV-Vis test results showed the best degradation at 30% ethanol variation with 34% at λ 250 nm.